2009
DOI: 10.1042/bst0371415
|View full text |Cite
|
Sign up to set email alerts
|

GABRB2 in schizophrenia and bipolar disorder: disease association, gene expression and clinical correlations

Abstract: The SCZ (schizophrenia)-associated GABA(A) receptor (gamma-aminobutyric acid type A receptor) beta(2) subunit gene GABRB2 was recently associated with BPD (bipolar disorder). Although weaker than its association with SCZ, significant association of GABRB2 with BPD was found in both German and Chinese, especially for the haplotypes rs1816071-rs187269 and rs1816072-rs187269 for which the M-M variants showed higher frequency in disease than the control. Significant genotype-dependent reduction in GABRB2 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…The full patient cohort, and the thus-separated ‘high PANSS score’ and ‘low PANSS score’ subgroups were each compared to the 117 healthy control subjects by means of the LRS test in UNPHASED. SNPs S1, S3 and S29 were significantly associated with SCZ in the full patient cohort in agreement with previous reports on association of GABRB2 SNPs with SCZ in Han Chinese [5], [41]. Interestingly, many of the association p -values of these SNPs with SCZ in the high PANSS score subgroup were drastically decreased to less than 10% of the full cohort p -values; e.g., the full cohort p -values for SNP S1 of 0.005 and 0.014 for allele and genotype associations, respectively, were decreased to 0.0004 and 0.001 in the high PANSS score subgroup (Table 2).…”
Section: Resultssupporting
confidence: 92%
“…The full patient cohort, and the thus-separated ‘high PANSS score’ and ‘low PANSS score’ subgroups were each compared to the 117 healthy control subjects by means of the LRS test in UNPHASED. SNPs S1, S3 and S29 were significantly associated with SCZ in the full patient cohort in agreement with previous reports on association of GABRB2 SNPs with SCZ in Han Chinese [5], [41]. Interestingly, many of the association p -values of these SNPs with SCZ in the high PANSS score subgroup were drastically decreased to less than 10% of the full cohort p -values; e.g., the full cohort p -values for SNP S1 of 0.005 and 0.014 for allele and genotype associations, respectively, were decreased to 0.0004 and 0.001 in the high PANSS score subgroup (Table 2).…”
Section: Resultssupporting
confidence: 92%
“…44, 45 Recently, GABRB2 has been associated with both bipolar disorder and schizophrenia. 89, 90, 91 Two novel isoforms of GABRB2 , β(2S1) and β(2S2) have also been associated with male subjects with bipolar disorder. 89 Moreover, Zhao et al , 89 by using quantitative real-time PCR, found that in post-mortem brain, there was significantly increased mRNA for β(2S1) in the DLPFC of subjects with bipolar disorder and significantly reduced mRNA for β(2S2) in DLPFC of subjects with bipolar disorder and schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, GABRB1, GABRA4, and GABRR1 are part of the same gene cluster on chromosome 4p12, together with GABRA2, while GABRA5 and GABRB3 are part of a cluster at 15q11-q13, which had previously been implicated in BPD 90 . Associations between nucleotide polymorphisms and BPD further exist for GABRA3 91 and GABRB2 92 , with the latter implicated in alternative splicing of the β2 subunit mRNA 93 . For MDD, genetic associations have been described for GABRA5 94 and the gene cluster encoding GABRA1 95,96 , GABRA6 and GABRG2 96 .…”
Section: Genetic Evidence In Support Of Gabaergic Deficits In Mood DImentioning
confidence: 95%